2020
DOI: 10.3390/s20216138
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Reflectance Can Differentiate Tracheal and Esophageal Tissue in the Presence of Bodily Fluids and Soot

Abstract: Endotracheal intubation is a common life-saving procedure implemented in emergency care to ensure patient oxygenation, but it is difficult and often performed in suboptimal conditions leading to high rates of patient complications. Undetected misplacement in the esophagus is a preventable complication that can lead to fatalities in 5–10% of patients who undergo emergency intubation. End-tidal carbon dioxide monitoring and other proper placement detection methods are useful, yet the problem of misplacement pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…In all instances, there was a statistically significant difference in ratios B and Y between the tissue types, which we hypothesized could be used as a means to validate tracheal tube placement if the technology was built directly into the tube. Furthermore, we confirmed that this difference persisted in the presence of saline, blood, vomit, or soot in the trachea in an initial attempt to simulate injury [17]. Herein, we hypothesized that not only would the tracheal spectral profile be present in live human tissue but that the trachea would continue to differ from other upper airway tissues, similar to the esophagus.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In all instances, there was a statistically significant difference in ratios B and Y between the tissue types, which we hypothesized could be used as a means to validate tracheal tube placement if the technology was built directly into the tube. Furthermore, we confirmed that this difference persisted in the presence of saline, blood, vomit, or soot in the trachea in an initial attempt to simulate injury [17]. Herein, we hypothesized that not only would the tracheal spectral profile be present in live human tissue but that the trachea would continue to differ from other upper airway tissues, similar to the esophagus.…”
Section: Discussionmentioning
confidence: 53%
“…Because inhalation injury results in airway edema and carbon deposits, it is unknown how it will affect tracheal spectral reflectance properties. In previous ex vivo work, however, we demonstrated that the presence of soot did not alter the tracheal spectral reflectance properties [17], but this finding awaits confirmation in actual patients with inhalation injury.…”
Section: Introductionmentioning
confidence: 46%